The Effect of The Realistic Mathematics Education (RME) Approach and The Initial Ability of Students on The Ability of Student Mathematical Connection - Febriyanti, Febriyanti; Bagaskorowati, Riana; Makmuri, Makmuri (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach and students' initial ability to mathematical connection skills of students in grade III of elementary school. The method used is the experimental method with 2x2 treatment by level design with 30 samples. Data analysis using two-way analysis of variance and followed by the Tukey test for the significance level Î± = 0.05. Test the normality of the data using the Lilliefors test and homogeneity test using the Bartlett test. The results of the study show that: 1). Mathematical connection skills in students taught by the Realistic Mathematics Education (RME) approach are higher than students taught by conventional approaches. 2). There is an interaction between the use of the learning approach and the students 'initial ability to students' mathematical connection skills. 3).Ability of mathematical connection of elementary school students between students who study using the Realistic Mathematics Education (RME) approach that has a high initial ability higher than students who learn by using a conventional approach that has high initial abilities. 4) The mathematical connection ability of elementary school students between students who study with the Realistic Mathematics Education (RME) approach that has low initial abilities is higher than students who learn with conventional approaches that have low initial abilities.